2013
DOI: 10.1111/nyas.12126
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of handgrip strength: age‐ and physical training–related changes in Lithuanian schoolchildren and conscripts

Abstract: Laterality in handgrip strength was assessed by analyzing dynamometric data of the right and left hand in three samples of Lithuanian boys and girls aged 7-20 years. In addition, the influence of general physical training on the laterality of handgrip strength was explored in a sample of conscripts. A negative secular trend in handgrip strength of schoolchildren has been detected since 1965, and with increasing age, right-handedness has become more pronounced. Children that were ambidextrous (by grip strength)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(107 reference statements)
3
5
0
Order By: Relevance
“…However, in girls, the absence of a mass component explaining the negative trend requires that we look elsewhere, namely changes in their lifestyle, especially increases in their sedentary activities and reductions in their involvement in daily chores/traditional games (Saranga et al, 2008). Similar results with comparable explanations were previously found in European girls (Tutkuviene and Schiefenhovel, 2013).…”
Section: Trends In Physical Fitness In Mozambican Youth 203supporting
confidence: 94%
“…However, in girls, the absence of a mass component explaining the negative trend requires that we look elsewhere, namely changes in their lifestyle, especially increases in their sedentary activities and reductions in their involvement in daily chores/traditional games (Saranga et al, 2008). Similar results with comparable explanations were previously found in European girls (Tutkuviene and Schiefenhovel, 2013).…”
Section: Trends In Physical Fitness In Mozambican Youth 203supporting
confidence: 94%
“…Hand grip strength for right-handed players was found greater in their dominant hand (comply with the 10% rule), but for the left-handed players the results were more equilibrated or even higher on their non-dominant hand (Bohannon, 2003;Hepping et al, 2015). During the study we have found the same results as authors mentioned above and others (Hepping et al, 2015;Tutkuviene & Schiefenhövel 2013;Incel et al, 2002;Bohannon, 2003), who claimed -that left-handed players were more often stronger on their non-dominant against their dominant hand in comparison with their right-handed rivals.…”
Section: Discussionsupporting
confidence: 85%
“…Grip strength in boys grew linearly with age in both hands until the 12th year. After that accelerated increase in strength for dominant hand occurred and for non-dominant hand we could observed the same tendencies after reaching the 13th year (Butterfield et al, 2009;Ploegmakers et al, 2013;Tutkuviene & Schiefenhövel 2013;Loffing et al, 2014;Hepping et al, 2015).…”
Section: Discussionsupporting
confidence: 69%
“…HGS can be influenced by many factors, such as age [11], gender [12], race [13], and exercise [14]. Nutritional status is one of the major determinants of HGS with aging.…”
Section: Introductionmentioning
confidence: 99%